Conferinţa internaţională „O abordare culturală a corupţiei. Relevanţa percepţiilor asupra corupţiei pentru prevenirea fenomenului" Cea de-a treia întâlnire a membrilor proiectului Dubrovnik, 17-21 ianuarie 2008 - Preoteasa, Ana Maria (Calitatea Vieții, 2008)
This is a presentation of an international meeting on corruption that was organised by the members of a research consortium dealing with “Crime as a Cultural Problem”. The various papers are mentioned and the research conclusions are briefly introduced with an emphasis on the methodology used, data collected and the explanatory models that resulted from the work of research consortium.